Sex hormone-binding globulin improves lipid metabolism and reduces inflammation in subcutaneous adipose tissue of metabolic syndrome-affected horses - Bourebaba, Lynda; Kępska, Martyna; Qasem, Badr; Zyzak, Magdalena; Łyczko, Jacek; Klemens, Marta; Mularczyk, Malwina; Marycz, Krzysztof (Frontiers in Molecular Biosciences, 2023)
Equine metabolic syndrome (EMS) is a steadily growing endocrine disorder representing a real challenge in veterinary practice. As a multifactorial condition, EMS is characterized by three main metabolic abnormalities including insulin resistance, increased adiposity or obesity and hoof laminitis. Adipose tissue dysfunction is recognized as a core pathophysiological determinant of EMS, as it strongly participates to lipotoxicity and systemic metaflammation, both of which have been closely linked to the development of generalized insulin resistance. Besides, sex hormone binding globulin (SHBG) is an important sex steroids transporters that has been recently proposed as an important metabolic mediator. Therefore, the aim of this study was to verify whether SHBG treatment may ameliorate subcutaneous adipose tissue metabolic failure under EMS condition in terms of lipidome homeostasis, lipid metabolism programs, insulin signalling and local inflammation. Subcutaneous adipose tissue (SAT) biopsies were collected post-mortem from healthy (n = 3) and EMS (n = 3) slaughtered horses. SHBG protein has been applied to SAT samples from EMS horses for 24 h at a final concentration of 50 nM, while control groups (healthy and untreated EMS) were cultured in the presence of SHBG-vehicle only. Tissues from all groups were afterwards secured for downstream analysis of gene expression using RT-qPCR, protein levels by Western blot and ELISA assay and lipidomics through GC-MS technique. Obtained results showcased that SHBG intervention efficiently normalized the altered fatty acids (FAs) profiles by lowering the accumulation of saturated and trans FAs, as well as the pro-inflammatory arachidonic and linoleic acids. Moreover, SHBG showed promising value for the regulation of adipocyte lipolysis and engorgement by lowering the levels of perilipin-1. SHBG exerted moderated effect toward SCD1 and FASN enzymes expression, but increased the LPL abundance. Interestingly, SHBG exhibited a negative regulatory effect on pro-adipogenic stimulators and induced higher expression of KLF3, IRF3 and β-catenin, known as strong adipogenesis repressors. Finally, SHBG protein showed remarkable ability in restoring the insulin signal transduction, IR/IRS/Pi3K/AKT phosphorylation events and GLUT4 transporter abundance, and further attenuate pro-inflammatory response by lowering IL-6 tissue levels and targeting the PDIA3/ERK axis. Overall, the obtained data clearly demonstrate the benefice of SHBG treatment in the regulation of adipose tissue metabolism in the course of EMS and provide new insights for the development of molecular therapies with potential translational application to human metabolic disorders.